Human Glomerular Endothelial Cells Treated With Shiga Toxin Type 2 Activate γδ T Lymphocytes - Rosso, David Antonio; Rosato, Micaela; Gómez, Fernando Daniel; Álvarez, Romina Soledad; Shiromizu, Carolina Maiumi; Keitelman, Irene Angélica; Ibarra, Cristina; Amaral, María Marta; Jancic, Carolina Cristina (Frontiers in Cellular and Infection Microbiology, 2021)
The hemolytic uremic syndrome associated with diarrhea, a consequence of Shiga toxin (Stx)-producing Escherichia coli infection, is a common cause of pediatric acute renal failure in Argentina. Stx type 2 (Stx2) causes direct damage to renal cells and induces local inflammatory responses which involve secretion of inflammatory mediators and the recruitment of innate immune cells. Gamma/delta T cells constitute a subset of T lymphocytes, which act as early sensors of cellular stress and infection. They can exert cytotoxicity against infected and transformed cells, and produce cytokines and chemokines. In this study, we investigated the activation of human peripheral gamma/delta T cells in response to the incubation with Stx2-stimulated human glomerular endothelial cells (HGEC) or their conditioned medium, by analyzing in gamma/delta T lymphocytes, the expression of CD69, CD107a, and perforin, and the production of TNF-alpha and IFN-gamma. In addition, we evaluated by confocal microscopy the contact between gamma/delta T cells and HGEC. This analysis showed an augmentation in cellular interactions in the presence of Stx2-stimulated HGEC compared to untreated HGEC. Furthermore, we observed an increase in cytokine production and CD107a expression, together with a decrease in intracellular perforin when gamma/delta T cells were incubated with Stx2-treated HGEC or their conditioned medium. Interestingly, the blocking of TNF-alpha by Etanercept reversed the changes in the parameters measured in gamma/delta T cells incubated with Stx2-treated HGEC supernatants. Altogether, our results suggest that soluble factors released by Stx2-stimulated HGEC modulate the activation of gamma/delta T cells, being TNF-alpha a key player during this process.